Improving Students’ Performance in Resolution of Vectors Using PhET Interactive Simulations - Acquah, Isaac Kwesi; Gyan, Michael; Appiah, Desmond; Ansah, Bright Owusu; Wilson, Robert; Mensah, Charles Enoch (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The paper examines the use of Physics Education Technology (PhET) simulations to enhance the academic performance of third-year science students at Kumasi Wesley Girls' High School. Methodology: The research used teacher-made tests, questionnaires, and informal observations to collect data. Ninety candidates (90 students) were selected from the third-year science population using a cluster sampling. The questionnaire, pre-evaluation, and post-evaluation tests on vectors were analyzed using descriptive statistics. Main Findings: The study found that PhET-based teaching significantly improved the performance of third-year science students in vector resolution, with a paired mean difference of 6.30 compared to pre-treatment tests. The questionnaire analysis of 90 students revealed that 85.6% initially found vector applications difficult, and 80% felt the teaching methods were unvaried and boring. After the PhET lab simulation intervention, 89% of students were enthusiastic about using simulations in future activities, and 78% reported an improved understanding of resultant vectors. The study indicates that PhET simulations significantly enhance student engagement and comprehension compared to traditional lecture teaching methods. Novelty/Originality of this study: The study explores using Physics Education Technology (PhET) simulations in Ghanaian high school Kumasi Wesley Girls' High School to improve vector resolution learning. The interactive approach demystifies complex concepts, and the study quantifies its impact on students' academic performance. It also provides insights into students' attitudes towards physics education